TURKEY RESPONSE TOWARDS CHINA DISCRIMINATIVE POLICY AGAINST UYGHUR PEOPLE - Ajeng Puspa Marlinda (HI 16 UMY 015, 2016)
*15 Uyghur is the Moslem ethnic who live in Xinjiang, west China, since the 2nd before centuries. The total population of Uyghur in Xinjiang is around 9 million people. However, they are one of the tribes in China who has the strong ethnicity relation with Turkey. They get the discrimination from China because they are not the original inhabitants of China. Even, China always accuses that Uyghur people are the terrorist who has the relation with Al-Qaeda and other terrorist organizations in the world. Many forms of China’s discriminative policies that had been done to Uyghur people. China does not want Uyghur dominate and control the Xinjiang because the wide of Xinjiang is one sixth of China. The climax happens when Uyghur Muslim is prohibited to do the fasting and read al-Qur’an in Ramadhan. It cannot be accepted by the citizens of Turkey and make the involvement of Turkey government to eliminate the discrimination of China toward the Moslems of Uyghur. This paper aims to explain about the response of Turkey towards China’s discriminative policy against their relative ethnic, the Moslems of Uyghur.